Unusual paralytic response to Amblyomma maculatum nymphal bite in alpha-gal knockout mice - Oyediran, Olaoluwa; Karim, Shahid (Frontiers in Arachnid Science, 2025)
The Gulf-Coast tick (Amblyomma maculatum) is an emerging species whose geographic range is expanding in the United States. Although tick bite-induced paralysis is uncommon, Am. maculatum has been implicated in cases affecting vertebrate hosts. We report a rare case of paralysis in α-Gal-deficient mice following nymphal tick attachment. Notably, the symptoms resolved rapidly after the nymph was removed.